Experimental study of the fracture of soft actuator beams - Phua, Yue Qi (2016)
Soft materials such as hydrogels, polymers and foams are increasingly adopted in biomedical and technological applications such as medical devices, robotics and actuators. Understanding the mechanical behaviours of soft materials would enhance the performance and reliability of machinery and devices that have incorporated soft materials in the manufacturing process. This project serves to analyse the effects of Mode I open loading on a double cantilever specimen fabricated from agar-gelatin. Two types of agar-gelatin are utilized in this study and subjected to similar forms of modification. Experiments that consist of variation in concentration, height and initial crack length are conducted respectively for the two types of agar-gelatin. Experimental data are thoroughly recorded in the Appendix and detailed graphical analyses are presented in this study. Double cantilever beam experiment allows the derivation of Young’s modulus based on a small initial region of the load against crack opening displacement graph that is assumed to be approximately linear and exhibits Hooke’s Law behaviour. Utilizing the maximum deflection equation of a cantilever beam subjected to a concentrated load at the free end and evaluation of second moment of area, Young’s modulus for each agar-gelatin specimen can be derived. Normalized graphs and application of Griffith’s theory provided further insights on agar-gelatin properties.